Multidisciplinary amyloidosis care in the era of personalized medicine - Bumma, Naresh; Kahwash, Rami; Parikh, Samir V.; Isfort, Michael; Freimer, Miriam; Vallakati, Ajay; Redder, Elyse; Campbell, Courtney M.; Sharma, Nidhi; Efebera, Yvonne; Stino, Amro (Frontiers in Neurology, 2022)
Amyloidosis refers to a group of conditions where abnormal protein – or amyloid – deposits in tissues or organs, often leading to organ malfunction. Amyloidosis affects nearly any organ system, but especially the heart, kidneys, liver, peripheral nervous system, and gastrointestinal tract. Neuromuscular deficits represent some of its ubiquitous manifestations. Nevertheless, amyloidosis can be quite challenging to diagnose given its clinical heterogeneity and multi-system disease manifestation. Early diagnosis with accurate genetic and serologic subtyping is important for effective management and prevention of organ decline. In this review, we highlight the value of a multidisciplinary comprehensive amyloidosis clinic. While such a model exists at numerous clinical and research centers across the globe, the lack of more widespread adoption of such a model remains a major hindrance to the timely diagnosis of amyloidosis. Such a multidisciplinary care model allows for the timely and effective diagnosis of amyloidosis, be it acquired amyloid light amyloidosis (AL), hereditary transthyretin amyloidosis (hATTR), or wild type amyloidosis (TTR-wt), especially in the current era of personalized genomic medicine. A multidisciplinary clinic optimizes the delivery of singular or combinatorial drug therapies, depending on amyloid type, fibril deposition location, and disease progression. Such an arrangement also helps advance research in the field. We present our experience at The Ohio State University, as one example out of many, to highlight the centrality of a multi-disciplinary clinic in amyloidosis care.